The Impact of Corporate Management on the Effectiveness of the Company - H. P. Karchilava; A. Yu. Bottaev (Управление, 2016)
Nowadays international examples show us that corporate management plays an important role in development of companies and international integration attracts useful and effective standards of corporate management other countries. In this article the main idea deals with influence of corporate management for efficiency of organization in all. There are few types of indicators that can assess the significance of corporate governance rating for the efficient functioning of the company, the rating, which is able to reflect all of the advantages and disadvantages of the company to stakeholders. However, those indicators don’t give us accurate results, because there are a lot of reasons which should be pointed. That’s why authors offer to use a model called “Balanced Scorecard”.